Six in family perish in car-lorry crash - Borneo Post, (KK) (Borneo Post, 2016)
GUA MUSANG: Six members of a family, including three children, were killed when their car was involved in a collision with a lorry at KM25 Jalan Gua Musang Kuala Krai near Kampung Rantau Manis here yesterday.